1993
DOI: 10.1038/364079a0
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian facilitative hexose transporters mediate the transport of dehydroascorbic acid

Abstract: Although vitamin C is critical to human physiology, it is not clear how it is taken up into cells. The kinetics of cell and tissue accumulation of ascorbic acid in vitro indicate that the process is mediated by specific transporters at the cell membrane. Some experimental observations have linked the transport of ascorbic acid with hexose transport systems in mammalian cells, although no clear information is available regarding the specific role(s) of these transporters, if any, in this process. Here we use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
415
2
9

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 485 publications
(442 citation statements)
references
References 27 publications
16
415
2
9
Order By: Relevance
“…Uptake and release of the two forms of vitamin C were found to be differentially affected by various reagents (Table 3), suggesting two separate transport mechanisms. In agreement with previous studies [29], DHA uptake was inhibited by reagents known to block mammalian glucose transport, including cytochalasin B and phloretin (Table 3). Importantly, cytochalasin D did not affect transport, precluding a non-specific interaction of the cytochalasins with the cell cytoskeleton to affect DHA uptake or AH release.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Uptake and release of the two forms of vitamin C were found to be differentially affected by various reagents (Table 3), suggesting two separate transport mechanisms. In agreement with previous studies [29], DHA uptake was inhibited by reagents known to block mammalian glucose transport, including cytochalasin B and phloretin (Table 3). Importantly, cytochalasin D did not affect transport, precluding a non-specific interaction of the cytochalasins with the cell cytoskeleton to affect DHA uptake or AH release.…”
Section: Resultssupporting
confidence: 92%
“…Further, perfusion studies in situ revealed that livers obtained from both rats and guinea-pigs released AH into the circulating perfusate. In agreement with previous studies [29], DHA uptake was mediated by glucose transporters in HepG2 cells. However, AH release from HepG2 cells seemed to be mediated by a separate temperature-sensitive mechanism that was susceptible to inhibition by phloretin and DIDS but was not affected by the glucose transport inhibitor cytochalasin B.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the substrate specificity of each isoform has n ot been firmly demonstrated. In fact, certain glucose transporters can transport a vitamin C derivative, an agent structurally unrelated to glucose (Vera et al 1993). Thus, it is possible that Glut-3 can transport an unknown material which is required for specialized cells such as the inner cell mass and pachytene spermatocytes.…”
Section: Function Of Oct-3 Downstream Genesmentioning
confidence: 99%
“…Several studies have demonstrated that the uptake and intracellular reduction of DHA from the surrounding interstitial space contributes to the maintenance of intracellular concentrations of AA. Transport studies have revealed that there are at least two different systems involved in the cellular uptake of vitamin C in mammalian cells ; a Na + -dependent co-transporter for AA [6], and a facilitative glucose transporter for DHA [7]. Following its uptake, DHA can be reduced to ascorbate in an enzymic or non-enzymic manner through a direct chemical reaction with reduced glutathione [8].…”
Section: Introductionmentioning
confidence: 99%